Prime minister decree 1486/2016 on the reorganization of the ministry of investment = قرار رئيس مجلس الوزراء رقم 1486 لسنة 2016 بإعادة تنظيم وزارة الاستثمار - Egypt; The middle east library for economic services, translator. (2025)
Prime Minister Decree No. 1486 Of The Year 2016 on the re-organization of the ministry of investment قرار رئيس مجلس الوزراء رقم 1486 لسنة 2016 بإعادة تنظيم وزارة الاستثمار